Unified interpretation of liver stiffness measurement by M and XL probes in non-alcoholic fatty liver disease. Issue 11 (18th January 2019) - Wong, Vincent Wai-Sun; Irles, Marie; Wong, Grace Lai-Hung; Shili, Sarah; Chan, Anthony Wing-Hung; Merrouche, Wassil; Shu, Sally She-Ting; Foucher, Juliette; Le Bail, Brigitte; Chan, Wah Kheong; Chan, Henry Lik-Yuen; de Ledinghen, Victor
Abstract : Objective: The latest model of vibration-controlled transient elastography (VCTE) automatically selects M or XL probe according to patients' body built. We aim to test the application of a unified interpretation of VCTE results with probes appropriate for the body mass index (BMI) and hypothesise that this approach is not affected by hepatic steatosis. Design: We prospectively recruited 496 patients with non-alcoholic fatty liver disease who underwent VCTE by both M and XL probes within 1 week before liver biopsy. Results: 391 (78.8%) and 433 (87.3%) patients had reliable liver stiffness measurement (LSM) (10 successful acquisitions and IQR:median ratio ≤0.30) by M and XL probes, respectively (p<0.001). The area under the receiver operating characteristic curves was similar between the two probes (0.75–0.88 for F2–4, 0.83–0.91 for F4). When used in the same patient, LSM by XL probe was lower than that by M probe (mean difference 2.3 kPa). In contrast, patients with BMI ≥30 kg/m 2 had higher LSM regardless of the probe used. When M and XL probes were used in patients with BMI <30 and ≥30 kg/m 2, respectively, they yielded nearly identical median LSM at each fibrosis stage and similar diagnostic performance. Severe steatosis did not increase LSM or the rate of false-positive diagnosis by XL probe. Conclusion: High BMI but not severe steatosis increases LSM. The same LSM cut-offs can be used without further adjustment for steatosis when M and XL probes are used according to the appropriate BMI.